Managing reputation through ranking: a case study of Universiti Teknologi MARA / Amirul Abd Rashid … [et al.] - Abd Rashid, Amirul; Janor, Roziah; Abd Rahman, Hayati; Mohamad Yusuwan, Norazian (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Being recognized as one of the best universities in the world has become priority for all academic institutions. In a range of strategic and operational decision-making scenarios, the ranking's performance serves as a proxy for educational quality, reflecting the university's standing. The measures taken by Universiti Teknologi MARA (UiTM) to unleash all its alternatives to establish itself as a leading provider of higher education using ranking outcomes are shared in this article. It will discuss the challenges and constraints that UiTM must face to meets the ranking requirement. Ranking metrics correlations to the improvement was presented particularly on indicators which focused on UiTM visibility efforts. The UiTM2025 blueprint, which leveraging on excellence, synergy, and integrity (ESI) principles supposed to transform UiTM into a top-tier global academic institution by the year 2025, includes ranking-related objectives as part of the strategies.